Role of extracellular polymeric substances in efficient chromium(VI) removal by algae-based Fe/C nano-composite. (November 2018) - Wu, Jun; Ma, Lin-Lin; Zeng, Raymond J.
Abstract: Subsequent application of the obtained algae by chemical coagulation (e.g. Fe(III) addition) presents a challenge because of various iron compounds in algae. In this study, algae obtained by chemical coagulation were carbonized to yield an algae-based Fe/C nano-composite with a high capacity for hexavalent chromium (Cr(VI)) removal (236.9 mg/g), which is attributed to the high reductive Fe content (e.g., FeS, Fe(0), and FeO) and specific surface area. The optimal conditions—that is, 100 mg/L Fe(III) addition and 800 °C—were determined. Moreover, the role of extracellular polymeric substances (EPS) in carbonization was examined as it affected the product composition and efficiency of Cr(VI) removal, owing to the stabilizing property effect of EPS in algae. Algal EPS induced the homogeneous distribution of Fe compounds on the surface of the algae, and the generated α-FeOOH nanoparticles were wrapped in organic carbon matrix, resulting in a sufficient reaction between Fe compounds and organic carbon during carbonization. X-ray photoelectron spectroscopy showed that reduction and adsorption contributed 83.44% and 16.56% to Cr(VI) removal, respectively. This study provides a new insight into the role of EPS in the efficient Cr(VI) removal by algae-based Fe/C nano-composite and presents a promising application of this Fe/C nano-composite in environmental remediation. Highlights: Optimal carbonization temperature and Fe(III) addition were determined. EPS results in high reductive Fe content and specific surface area. EPS affects Cr(VI) removal efficiency of the Fe/C composite owing to the stabilizing property. Algae-based Fe/C nano-composite has a 236.9 mg/g removal capacity for Cr(VI).